Técnicas activas aplicadas en la asignatura desarrollo del pensamiento y su influencia en el proceso de enseñanza aprendizaje en los estudiantes de los octavos años de educación básica sección nocturna del Colegio Nueve de Octubre de la ciudad de Machala, durante el período lectivo 2010-2011. - Bolaños Rosero, Richard Segundo (2011)
Finally, with the structure of the proposal, called guide active techniques aimed at improving cognitive and metacognitive skills in the process of learning of the subject Development Thought the eighth year of basic education, a contribution that will allow educators potentiate their intellectual abilities, therefore, allows teachers to apply active techniques in a process-which helps to improve the development of intellectual abilities.